PENGARUH HARGA FASILITAS DAN KEPUTUSAN MENGINAP TERHADAP KEPUASAN TAMU DI MULTAZAM SYARIAH HOTEL SOLO - Agung Riyanto; Andhi Supriyadi (LPSDI Bina Patria, 2024)
This study intends to find out how price, facilities and staying decisions influence guest satisfaction which is mediated by the decision to stay at the Multazam Syariah Hotel Solo. This research is inferential research which emphasizes the analysis of numerical data which is processed using statistical methods, namely examining the factors that occur and the results of this research will illustrate the relationship between price and facilities on guest satisfaction based on the decision to stay at the Multazam Syariah Hotel Solo. The sample for the study used 85 respondents from guests staying at the Multazam Syariah Hotel Solo. The data collection method using questionnaires was tested and analyzed using multiple linear regression using SPSS. From the results of data processing in research, several conclusions can be proposed (1) Price has no influence on guest satisfaction (2) Facilities have an influence on guest satisfaction (3) Decision to stay has an influence on guest satisfaction (4) Influence of price, facilities and guest satisfaction The decision to stay has a collective influence.